The Alignment of Accounting Curriculum with Market Requirements: The Iraqi Case - Ramadhan, Sherzad; Aridah, Mamoun Walid; Alkoutaini, Hasan; Ahmed, Fareeba; Khorsheed, Hariwan; Obaied, Shamal; Amar, Aldulaimi (European Scientific Journal, ESJ, 2024)
This research investigates the alignment between Iraqi university accounting courses and industry demands to enhance the standard and relevance of accounting education. The primary research method was a questionnaire, aiming to understand how well accounting courses at Iraqi institutions meet market requirements. The study’s methodology comprised two parts: examining the current accounting curriculum and conducting a follow-up survey using diverse sources and analytical techniques. A total of 350 surveys were distributed to academics and employers, yielding 87 responses from academic staff and 102 valid responses from employers. The study analyzed the latest accounting curriculum, demographic data, relevance ratings for courses, and assessments of essential work skills using SPSS software. Results revealed diverse demographics, with significant responses from academics (58%) and employers (51%). Findings indicate both convergence and divergence in the perceived importance of specific accounting courses, suggesting gaps between theoretical concepts and practical applications. The report underscores the need to align Iraq’s accounting curriculum with business needs. Recommendations include systematic curriculum assessments, increased industry-academia collaboration, continual professional development for educators, and a broader focus on skills. This study provides evidence-based suggestions for improving accounting education in Iraq to meet evolving market demands.